2013
DOI: 10.1371/journal.pone.0059729
|View full text |Cite
|
Sign up to set email alerts
|

Critical Structure Sparing in Stereotactic Ablative Radiotherapy for Central Lung Lesions: Helical Tomotherapy vs. Volumetric Modulated Arc Therapy

Abstract: BackgroundHelical tomotherapy (HT) and volumetric modulated arc therapy (VMAT) are both advanced techniques of delivering intensity-modulated radiotherapy (IMRT). Here, we conduct a study to compare HT and partial-arc VMAT in their ability to spare organs at risk (OARs) when stereotactic ablative radiotherapy (SABR) is delivered to treat centrally located early stage non-small-cell lung cancer or lung metastases.Methods12 patients with centrally located lung lesions were randomly chosen. HT, 2 & 8 arc (Smart A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Deaths related to pulmonary or cardiopulmonary dysfunction due to high-dose delivered by 3D-CRT and IMRT are the most likely explanations for the outcomes of the RTOG 0617 (19). It can be reasonably assumed that more advanced radiotherapy technologies should be employed when high dose of radiation are applied to patients with locally advanced NSCLC, which brings us to the HT, a novel platform that has already shown the good ability in OARs sparing and can define the target more accurately in various sizes (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Deaths related to pulmonary or cardiopulmonary dysfunction due to high-dose delivered by 3D-CRT and IMRT are the most likely explanations for the outcomes of the RTOG 0617 (19). It can be reasonably assumed that more advanced radiotherapy technologies should be employed when high dose of radiation are applied to patients with locally advanced NSCLC, which brings us to the HT, a novel platform that has already shown the good ability in OARs sparing and can define the target more accurately in various sizes (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…15 However, in the previous studies, HT was better in protection of surrounding tissues than VMRT and IMAT. 10,11 Therefore, whether the low-dose irradiation of large lung volumes or the high-dose irradiation of small lung volumes may be the main cause for pneumonitis is still uncertain. It is still controversial that whether low dose with high volume radiation or high dose with low volume radiation induces pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Compared with intensity-modulated RT (IMRT), single-arc intensity-modulated arc therapy (IMAT), 3-dimensional conformal RT (3D-CRT), volumetric-modulated arc therapy (VMAT), and helical tomotherapy (HT) may be superior to organs at risk (OARs) sparing and to providing higher target dose uniformity. [7][8][9][10] Recently, HT appears to be superior to VMAT in OAR sparing mainly in central lung cancer that requires conformal dose avoidance of multiple immediately adjacent OARs. 11 However, most studies focused on either central lung cancer or peripheral lung cancer in the early stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CN 100 in coplanar VMAT and non-coplanar flattening filter-free VMAT are 0.79 and 0.81, respectively. 18 Chi et al 24 showed relatively lower CN 100 values of 0.61-0.64, calculated for the helical tomotherapy and VMAT plans. The CN 100 value of 0.72 in this report was comparable with the results of those studies.…”
Section: Lomax and Scheibmentioning
confidence: 96%